Multipath Discovery Algorithms for VoD Streaming In Wireless Mesh Network - Ramteke, Praful Chandrakant; Jadhav, V.S.; Wadekar, Raju (Discoveries in Agriculture and Food Sciences, 2015)
Transmission and routing of video data over wireless network is a challenging task because of wireless interferences. To improve the performance of video on demand transmission over wireless networks multipath algorithms are used. IPD/S (Iterative path discovery/selection) PPD/S (Parallel Path discovery/selection) are two algorithms which is used for discovering maximum number of edge disjoint paths from source to destination, for each VoD request by considering the effects of wireless interferences. In this paper performance evaluation of these multipath discovery algorithms for VoD (Video on demand) streaming in wireless mesh network is presented. These algorithms are evaluated on the bases of Number of Path discovers, Packet drop ratio and delay. Simulation result shows that PPD/S works batter as compared to IPD/S because it’s able to discover more paths than IPD/S under same circumstances.